Pre-Hospital Point-of-Care Troponin: Is It Possible to Anticipate the Diagnosis? A Preliminary Report - Cristian Lazzari; Sara Montemerani; Cosimo Fabrizi; Cecilia Sacchi; Antoine Belperio; Marilena Fantacci; Giovanni Sbrana; Agostino Ognibene; Maurizio Zanobetti; Simone Nocentini (Diagnostics)
Background: Thanks to the evolution of laboratory medicine, point-of-care testing (POCT) for troponin levels in the blood (hs-cTn) has been greatly improved in order to quickly diagnose acute myocardial infarction (AMI) with an accuracy similar to standard laboratory tests. The rationale of the HEART POCT study is to propose the application of the 0/1 h European Society of Cardiology (ESC) algorithm in the pre-hospital setting using a POCT device (Atellica VTLi). Methods: This is a prospective study comparing patients who underwent pre-hospital point-of-care troponin testing (Atellica VTLi) with a control group that underwent standard hospital-based troponin testing (Elecsys). The primary objectives were to determine if the 0/1 h algorithm of the Atellica VTLi is non-inferior to the standard laboratory method for diagnosing AMI and to analyze rule-out/rule-in times and emergency department (ED) stay times. The secondary objective was to evaluate the feasibility of pre-hospital troponin testing. Results: The Atellica VTLi demonstrated reasonable sensitivity for detecting AMI, with sensitivity increasing from 60% at the first measurement (time 0) to 80% at the second measurement (time 1 h). Both the Atellica VTLi and the Elecsys method showed high negative predictive value (NPV), indicating that a negative troponin result effectively ruled out AMI in most cases. Patients in the Atellica VTLi group experienced significantly shorter times to diagnosis and discharge from the emergency department compared to the control group (Elecsys). This highlights a potential benefit of point-of-care testing: streamlining the diagnostic and treatment processes. Conclusions: POCT allows for rapid troponin measurement, leading to a faster diagnosis of non-ST-segment elevation myocardial infarction (NSTEMI). This enables earlier initiation of appropriate treatment, potentially improving patient outcomes and the efficiency of emergency department operations. POCT could be particularly beneficial in pre-hospital settings, enabling faster triage and transportation of patients to appropriate care centers.